Effects of self-modeling on figure skating jump performance and psychological variables - Law, B.; Ste-Marie, D. M. (European Journal of Sport Science, 2005)
This study investigated whether self-modeling plus physical practice would improve intermediate level figure skaters` jump performance, as well as their self-efficacy, motivation, and state anxiety, when compared to physical practice alone. Twelve female figure skaters (M=13.4 years of age, SD=1.4) participated in a within-participant design where they received a self-modeling intervention for one jump and a control condition for another jump. They were also compared with a separate control group of 7 skaters (M=14.2 years of age, SD=2.35) who received no intervention. We hypothesized that skaters would show greater improvement in physical and psychological performance scores for jumps in the self-modeling condition than for jumps in the control conditions. We also hypothesized that increased self-efficacy and motivation and decreased state anxiety would mediate the relationship between self-modeling and physical performance. Counter to our predictions, no differences existed between the two conditions for the self-modeling group or between the self-modeling group and the control group. Despite the lack of statistical support for our hypotheses, skaters` evaluation of the intervention was very positive and suggests possible explanations for the results.